2010
DOI: 10.1007/s11999-009-0961-0
|View full text |Cite
|
Sign up to set email alerts
|

Does Severity or Specific Joint Laxity Influence Clinical Outcomes of Anterior Cruciate Ligament Reconstruction?

Abstract: It generally is believed generalized joint laxity is one of the risk factors for failure of anterior cruciate ligament (ACL) reconstruction. However, no consensus exists regarding whether adverse effects on ACL reconstruction are attributable to joint-specific laxity or are related to the severity of generalized joint laxity. We therefore asked whether knee stability and functional outcomes would be related to joint-specific laxity and would differ according to the severity of generalized joint laxity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 22 publications
0
50
0
Order By: Relevance
“…Furthermore, it is well documented in the literature that in a ACL‐deficient knee the menisci play an important role as secondary restraints as well (Noyes et al., ; Johnson & Coen, ). Moreover, in chronic cases a progressive stretching of the secondary restraints, especially on the lateral capsular structures, often occurs (Kim et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it is well documented in the literature that in a ACL‐deficient knee the menisci play an important role as secondary restraints as well (Noyes et al., ; Johnson & Coen, ). Moreover, in chronic cases a progressive stretching of the secondary restraints, especially on the lateral capsular structures, often occurs (Kim et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…For the previously mentioned reasons, the correct intraoperative evaluation of secondary restraints status remains an important issue. Controversy exists regarding the importance of pre‐reconstruction knee laxity as a potential risk factor for the ACL reconstruction outcome failure (Kim et al., ). Especially, there is a lack of studies focused on the analysis of knee laxity values before ACL reconstruction, and how the latter affect the post‐reconstruction outcome.…”
mentioning
confidence: 99%
“…A recent study also reported inferior results after an ACL reconstruction in patients with excessive ligament laxity, but the results were not significant 6). Patients with excessive knee hyperextension showed inferior results after a reconstruction 65). Laxity of the secondary knee restraints and the increased graft impingement against the intercondylar roof might be the contributing factors for the negative effects of knee hyper extension on a reconstructed graft.…”
Section: Reconstruction Options and Graft Selectionmentioning
confidence: 97%
“…There is still no consensus on whether knee hyperextension affects the outcomes following ACL-R. Two studies10 13 showed significant associations between knee hyperextension and inferior outcomes following ACL-R. Kim et al 10 investigated the effect of knee hyperextension on postoperative outcomes and found that knee hyperextension of more than 10° is correlated with greater postoperative anterior tibial translation measured by KT-2000 (ρ=0.461) and inferior Lysholm (ρ=−0.285) and IKDC scores (ρ=−0.285). Recently, Larson et al 13 have shown that heel height greater than 5 cm, as a measure of knee hyperextension, was an independent predictor of ACL failure.…”
Section: Discussionmentioning
confidence: 99%